Impact of carrion decomposition on topsoil chemistry and their eco-forensic implications in a Southern Nigerian ecosystem - Oghenefego Michael Adheke; Loveday Ese Oghenemavwe; Darlington Nnamdi Onyejike; Josiah Soipiriala Hart; Bassey Udom; Terkuma Fredrick Ujoh (Acta Scientiarum. Biological Sciences, 2025)
Post-mortem interval (PMI) is the period since death of human or animal remains upon discovery. Studying the soil chemical properties could provide a taphonomic approach of carrion decay. The present study aimed to examine the relationships between soil chemical properties and decomposition timeline of remains at both dry and wet seasons in a Southern Nigerian (Port Harcourt) ecosystem. Using an observational, analytical design during the dry (December 2022 to February 2023) and wet season (3rd to the 18th of April 2023), healthy pigs (Sus scrofa domesticus) weighing between 40 – 60 kg were used. Upon euthanization, pigs were buried at different cadaver decomposition islands (CDIs) within the site and at weekly intervals. Pig carrion decomposition was scored quantitatively using the Keough et al. total body score (TBS) method based on the observed morphological appearance of selected body regions. Soil samples were collected, air-dried, sieved, and analyzed for chemical properties using standard analytical procedures. Statistical differences in soil chemical characteristics between post-mortem intervals were performed using both one-way analysis of variance (ANOVA) and Post Hoc tests. From the results, pH levels of dry and wet season gravesoil samples differed significantly at various PMIs (p < 0.05) in comparison with control soil samples. Calcium and magnesium levels were increased on days 7 (mean TBS of 16.3) and 14 (mean TBS of 21.3) while potassium concentrations elevated significantly at both days 14 in both seasons. There were significant increases in sodium concentration on day 7 (at a mean TBS of 19.3) for the wet season. Exchangeable acidity (EA) and effective cation exchange capacity (ECEC) values increased significantly in both study periods. The study showed significant associations between the post-mortem intervals of study pig carcasses and variations in chemistry of the gravesoil samples.